Zakat as a Special Institution of Public Finance: Reflections from Kitab Al-Amwal of Abu 'Ubayd (d.224/838) - Suharto, Ugi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Zakat as a Special Institution of Public Finance: Reflections from Kitab Al-Amwal of Abu 'Ubayd (d.224/838)